The Influence of Discipline and Training on Teacher Performance in Junior High Schools - Juniardi, Yusuf; Irwan Lakawa; hujiyanto (International Journal of Management and Education in Human Development, 2022)
Today the development of construction projects is fast and often on a large scale requires large costs and has methods that can improve the quality of planning and control to deal with the number of complex project activities that sometimes increase. A construction project is a series of activities that are only carried out once and have a limited time where the end and beginning of the project are relatively certain. The implementation of repetitive (repetitive) work on construction projects does not always have to be completed for one item of activity first and then for the second, third, and so on. This is definitely ineffective in the use of resources, and duration, and has the effect of increasing project costs. Implementation of multi-item projects characterized by work? Repetitive work should be engineered for more effective use of resources by grouping workers from one work item to another. The success of a construction project is highly dependent on scheduling and planning. This study applies the Line Of Balance (LoB) method to project scheduling where initially the project was planned using the S Curve method. Line of Balance is a variation of the linear scheduling method that allows the balance of operations so that each activity can continue. The project is The Park Kendari Builder. In this study, the research method in calculating using the Line of balance was carried out. Conflict analysis was carried out after drawing into the line chart the results of the planner's calculations using the Line of Balance (LoB) method. Conflict analysis and drawing diagrams obtained the final duration of work of 56 weeks.